Chemical Validation of DegS As a Target for the Development of Antibiotics with a Novel Mode of Action. (24th April 2019) - Bongard, Jens; Schmitz, Anna Laura; Wolf, Alex; Zischinsky, Gunther; Pieren, Michel; Schellhorn, Birgit; Bravo‐Rodriguez, Kenny; Schillinger, Jasmin; Koch, Uwe; Nussbaumer, Peter; Klebl, Bert; Steinmann, Jörg; et al.
Abstract: Despite the availability of hundreds of antibiotic drugs, infectious diseases continue to remain one of the most notorious health issues. In addition, the disparity between the spread of multidrug‐resistant pathogens and the development of novel classes of antibiotics exemplify an important unmet medical need that can only be addressed by identifying novel targets. Herein we demonstrate, by the development of the first in vivo active DegS inhibitors based on a pyrazolo[1, 5‐ a ]‐1, 3, 5‐triazine scaffold, that the serine protease DegS and the cell envelope stress‐response pathway σE represent a target for generating antibiotics with a novel mode of action. Moreover, DegS inhibition is synergistic with well‐established membrane‐perturbing antibiotics, thereby opening promising avenues for rational antibiotic drug design. Abstract : Synergism : The development of small‐molecule DegS inhibitors enabled validation of the bacterial HtrA S1 serine protease DegS and the outer membrane stress‐response pathway as targets for the development of antibiotics with a novel mechanism of action. Importantly, these DegS inhibitors were found to act synergistically with established membrane‐perturbing antibiotics such as colistin.